Influence of differences in take-off surface hardness on rebound drop jumping skills and jumping movements of gymnasts and field jumping/combined athletes - Motoshima, Y.; Komori, D.; Kitagawa, J.; Maeda, A. (Japan Journal of Physical Education, Health and Sport Sciences, 2015)
This study examined the influence of differences in take-off surface hardness on rebound drop jumping skills and jumping movements, involving gymnasts and field jumping/combined athletes. The participants performed rebound drop jumps from a 30-cm-high platform with a hard surface using (spring) or not using (non-spring condition) a springboard, and their movements were measured with an optical three-dimensional motion analysis system (Mac3D) and a multi-component force plate. The jumping height and the RDJ index were significantly greater under the spring than the non-spring condition (p<0.01). Under both conditions, the jumping/combined athletes showed markedly higher jumping height than the gymnasts (p<0.05), the gymnasts showed a markedly shorter contact time than the jumping/combined athletes (p<0.001). Furthermore, under the spring condition, there were no significant differences in RDJ index values among the events. These results show that RDJ index-related factors under the spring condition varied among the events. In addition, gymnasts have mastered an effective jumping motion in order to effectively store elastic energy in the spring from the surface by increasing their leg stiffness. On the other hand, jumping/combined athletes have mastered an effective jumping motion in order to effectively store elastic energy in the lower limbs through the bending and stretching motion of their lower limbs.